Tendencia de la Industria 4.0 comparado con Industria 5.0 - Luis Asunción Pérez-Domínguez; José Roberto Ávila-Lopez; David Luviano-Cruz (Mundo Fesc)
This study explores the literature on Industry 4.0 compared to Industry 5.0. The study explores the course of industrial progress, marked by the emergence of disruptive technologies that trigger revolutions with significant social and economic impact. Similar to the analysis of how Industry 4.0 involves humans using technology to monopolize the generation of knowledge and intelligence, Industry 5.0 aims to generate this knowledge and intelligence from machines themselves. This new era in industry suggests that collaborative robots (cobots) will become more prevalent in the coming years, along with the deployment of intelligent software (bots). This will pave the way for a new concept of economic and industrial development. With the return of humans to the process and the production model, the integrative relationship between humans and technology takes on new meaning. Finally, this article documents the review of the literature that was published on the topic of Industry 4.0 and Industry 5.0, the articles were reviewed and researched in different databases and in high-ranking journals in order to obtain the best understanding of both industries.